2014
DOI: 10.1128/jvi.01965-14
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Clinical Strains of Human Parainfluenza Virus Reveal Viral Entry Requirements for In Vivo Infection

Abstract: Human parainfluenza viruses (HPIVs) cause widespread respiratory infections, with no vaccines or effective treatments. We show that the molecular determinants for HPIV3 growth in vitro are fundamentally different from those required in vivo and that these differences impact inhibitor susceptibility. HPIV infects its target cells by coordinated action of the hemagglutininneuraminidase receptor-binding protein (HN) and the fusion envelope glycoprotein (F), which together comprise the molecular fusion machinery; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(79 citation statements)
references
References 40 publications
7
72
0
Order By: Relevance
“…CX3CR1 is expressed in epithelial cells, smooth muscle cells, microglia, neurons, T cells, monocytes, dendritic cells, and NK cells [47][48][49][50][51][52][53]. RSV is able to infect nearly all immortalized cell lines and infects primary epithelial cells, smooth muscle cells, neuronal cells, eosinophils, and dendritic cells [19,40,54,55]. Here we found that CX3CR1 is detectable on the cilia of ciliated cells in HAE cultures, the cell targeted by RSV [19].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…CX3CR1 is expressed in epithelial cells, smooth muscle cells, microglia, neurons, T cells, monocytes, dendritic cells, and NK cells [47][48][49][50][51][52][53]. RSV is able to infect nearly all immortalized cell lines and infects primary epithelial cells, smooth muscle cells, neuronal cells, eosinophils, and dendritic cells [19,40,54,55]. Here we found that CX3CR1 is detectable on the cilia of ciliated cells in HAE cultures, the cell targeted by RSV [19].…”
Section: Discussionmentioning
confidence: 56%
“…Differences in measles virus (MV) receptor usage between clinical isolates and laboratory strains have been well documented to be due to selection during growth in immortalized cells. SLAM (CD150) is used as a receptor by clinical isolates [40], but not by the laboratory adapted Edmonston strain of MV which uses CD46 [56]. Because mAb 131-2g blocks G protein binding to CX3CR1, our finding that mAb 131-2g neutralizes infection of clinical isolates for HAE cultures (Fig 1D) indicates that the use of CX3CR1 is not an artifact of using a laboratory strain of RSV.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The attachment protein's F-activating region then interacts with an exposed hydrophobic loop in the IgG-like domain of F to provide the energy needed to promote F refolding and membrane fusion (4,5). This energy barrier to the activation of F can also be overcome by increased temperature (6)(7)(8)(9)(10) or by the introduction of destabilizing point mutations (11)(12)(13). The paramyxovirus parainfluenza virus 5 (PIV5) WR isolate differs in sequence from the W3A isolate by only three residues: the L22, P443, and A516 in WR are P22, S443, and V516 in W3A (14).…”
mentioning
confidence: 99%
“…F itself influences the extent and timing of fusion through its prefusion stability, kinetics of activation, and precursor cleavability. Fusion is moderated through a balance of these functions of HN and F. While viruses bearing the fusion complex of clinical strains grow efficiently in both the human airway and in vivo models, they fail to grow on immortalized cells, demonstrating the profound specificity of the HN/F complex for the authentic host (28,30).…”
mentioning
confidence: 99%